Brand Experience and Service Quality: Key Drivers of Customer Satisfaction in Gojek Apps - Ningsih, Tasya Septia; Nasution, Muhammad Dharma Tuah Putra; Robain, Wilchan (IJBLE Scientific Publications Community Inc., 2024)
This study analyzes the impact of brand experience and perceived service quality on customer satisfaction with Gojek and its implications in the context of transportation services. Using a quantitative method, primary data were collected from students at Universitas Pembangunan Panca Budi who used Gojek's services. The analysis indicates that both brand experience and perceived service quality significantly influence customer satisfaction. These findings complement previous research highlighting the crucial role of customer satisfaction in branding. The practical implications of this study underscore the importance for Gojek to focus on brand experience and service quality to enhance customer satisfaction and maintain its competitiveness in the digital transportation service market.